Experimental Studies on the effects of chlorpyrifos on Rats II. Histochemical changes - S. H.. El-durssi, Ibrahim; I. O. El-Awami, Ifdial; mahmoud, Ghyath; A. Benkhaial, Fahim (Al-Mukhtar Journal of Sciences, 2006)
This Study performed to investigate the effect of Chlorpyrifos (one of the most used insecticides)on certain organs in rats . The experimental animals were 110 male rats and were divided into four groups: the first group was used to determine the median lethal dose (LD50) which appeared to be equal to (81.2)mg/Kg B.W. While the second group of rats received an oral daily doses of 1/10 LD50. The third and fourth groups of rats were administered single oral dose of 1/10 LD50 and 1/30 LD50 respectively. Although histochemical investigation revealed that the epithelial cells of the intestine, liver biliary system and kidney’s tubules both in control and experimental rats contained a mixture of acid and neutral mucopolysaccharidse. This reaction matching the histochemistry of both the mast cells and goblet cells in control and experimental rats.